Canadian Gallup Poll, March 1973, #358 - Gallup Canada (Borealis, 2019)
This Gallup poll seeks the opinions of Canadians, on both political and social issues. The questions ask opinions about political leaders and political issues within the country. There are also questions regarding movies, parole for re-offenders and white collar workers. The respondents were also asked questions so that they could be grouped according to geographical variables. Topics of interest include: allowing prisoner with a prior record to go on parole; creating a union for white collar workers; the changing attitudes towards illegitimacy; the date a movie was last attended; the degree of honesty in wives; the effects of a minority government; the effects of the Federal budget; the effect of the Mackenzie Valley Pipeline; whether or not the respondent gets the amount of respect deserved; interest in Canadian films; how interesting movies are; nationalizing energy resources; opinions about Lewis; opinions about Stanfield; opinions about Trudeau; rating the Federal budget; requiring theatres to show Canadian films; sending Canadian troops to Vietnam; and wage and price controls. Basic demographic variables are also included.